2020
DOI: 10.1111/pedi.13056
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pancreatic exocrine function in young at‐risk children followed to islet autoimmunity and type 1 diabetes in the ENDIA study

Abstract: Full title:Changes in pancreatic exocrine function in young at-risk children followed to islet autoimmunity and type 1 diabetes in the ENDIA study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…Indeed, lipase levels were more variable compared with trypsinogen, which could be a contributing factor. Although longitudinal studies are needed to further address the ability of pancreatic exocrine enzymes to predict disease stage and progression, our data are in line with a recent report from the Environmental Determinants of Islet Autoimmunity (ENDIA) study demonstrating that fecal elastase-1 levels decline longitudinally in at-risk children who eventually diabetes.diabetesjournals.org develop islet autoimmunity and type 1 diabetes (39). Serological markers are likely of greater clinical utility given historical challenges surrounding patient compliance with fecal tests (40).…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, lipase levels were more variable compared with trypsinogen, which could be a contributing factor. Although longitudinal studies are needed to further address the ability of pancreatic exocrine enzymes to predict disease stage and progression, our data are in line with a recent report from the Environmental Determinants of Islet Autoimmunity (ENDIA) study demonstrating that fecal elastase-1 levels decline longitudinally in at-risk children who eventually diabetes.diabetesjournals.org develop islet autoimmunity and type 1 diabetes (39). Serological markers are likely of greater clinical utility given historical challenges surrounding patient compliance with fecal tests (40).…”
Section: Discussionsupporting
confidence: 88%
“…Exocrine pancreas dysfunction is commonly accepted as a feature of type 1 diabetes, as evidence from multiple independent studies have shown decreased levels of pancreatic enzymes [15][16][17][18][27][28][29][30]. In this study, we demonstrate that impaired exocrine function, resulting in lower levels of circulating P-amylase and lipase, can be detected long before the onset of clinical symptoms in at-risk adult individuals, but not in children.…”
Section: Discussionsupporting
confidence: 47%
“…To strengthen these results, a validation cohort would be needed. Reduced levels of FE-1 [16], serum trypsinogen [17] and lipase [18] have been reported in children at-risk of developing type 1 diabetes. In our analysis, we have taken into account the effect of multiple parameters (such as age, sex and number of autoantibodies) on P-amylase and lipase levels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This suggests that pancreatic shrinkage is already ongoing in pre-diabetes. In a study of 85 children participating in the ENDIA study, levels of Fecal Elastase-1, another marker of pancreatic function, were shown to decrease over time in 28 progressors compared to non-progressors ( 60 ). A study of TrialNet participants at diagnosis and in those with islet autoantibodies showed that lower levels of circulating P-amylase and lipase (both exocrine enzymes) can be detected before the onset of clinical symptoms in at-risk adult individuals, but not in children ( 61 ).…”
Section: Monitoring Efficacy In Clinical Trialsmentioning
confidence: 99%